Transformational Leadership and Employer Branding with Job Satisfaction Mediation on Customer Loyalty Outcomes among MSMEs - Hendra Armadhan Hariyanto Hariyanto; Subroto Alirejo Alirejo (International Journal Business and Entrepreneurship, 2026)
This study examines how transformational leadership and employer branding influence customer loyalty through job satisfaction among MSMEs in Purwakarta. Using a quantitative design, data were collected from 205 MSME employees and analyzed with SEM-PLS. Results indicate that transformational leadership and employer branding significantly increase job satisfaction. Job satisfaction, in turn, has a strong positive effect on customer loyalty and mediates the effects of leadership and branding on loyalty. The model explains substantial variance in job satisfaction and moderate variance in customer loyalty, confirming the relevance of internal management practices for market outcomes. The findings support the Attitude–Behavior–Outcome framework by showing that organizational inputs shape employee attitudes that translate into customer responses. Practically, the study suggests that MSMEs can strengthen loyalty by investing in inspirational leadership and consistent employer branding that enhances employee satisfaction. These strategies are feasible for small firms because they rely more on interpersonal practices than on financial resources. This research extends leadership and employer branding literature to the MSME context and highlights job satisfaction as a key transmission mechanism between internal and external performance. Policy implications are relevant for local enterprise development programs in Indonesia contexts.